Manajemen Pembelajaran Leadership Nirkekerasan pada Anak Didik di Madrasah - Syamsul Kurniawan (Raheema, 2015)
Based on the facts and society complaints on National Child Protection Commission along 2010-2014, the commission concludes that nowadays Indonesia is in the state of “emergency” especially for child violences. Furthermore, the numerous cases of student abuse in madrasah highly rise. This writing elaborates how to manage the leadership and non-violence study towards student in madrasah. Moreover, the action is implemented without violence acts and languages.